Identification of Phenolic Compounds in Aleppo Oak - Apple and Study its Effect on Types of Bacteria and Candida - Siddeek Bakr Mar'ie; Suha Saeed Rashid Al-Tikrit; Ayad C. Khorsheed (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study investigated the phytochemical screening and antibacterial activity against various microorganisms including E. coli, Staphylococcus aureus, Klebsiella pneumoniae, Enterococcus faecalis, and Candida albicans. Active compounds were isolated and identified from Aleppo Oak Gallnut, obtained from the Iraqi plant Quercus Infectoria L. Plant extracts were prepared using a continuous extraction apparatus, Soxhlet, with a successive solvent system based on polarity differences, including petroleum ether (60-80°C), ethanol (78°C), and hot aqueous extracts. Acid hydrolysis was performed on the raw ethanol and hot water extracts to obtain free phenolic compounds, including Gallic acid, Apigenin, Rutin, Kaempferol, Chlorogenic acid, and Caffeic acid, using high-performance liquid chromatographic (HPLC) techniques. The inhibitory activity of Aleppo Oak Gallnut extracts (Ethanol and Hot Aqueous) after acid hydrolysis was tested using four concentrations (25%, 50%, 75%, 100%) against various microorganisms. The Ethanol extract exhibited a significant inhibitory effect on Enterococcus faecalis. The Hot Aqueous extract showed a modest inhibitory effect on Enterococcus faecalis. The Ethanol extract demonstrated strong inhibition against Klebsiella pneumoniae. The Hot Aqueous extract at 100% and 75% showed high inhibition. The Ethanol extract exhibited significant inhibitory effects against Staphylococcus aureus at 100%. The Hot Aqueous extract at 75% and 100% demonstrated weaker inhibition against Staphylococcus aureus. The Ethanol extract demonstrated weaker inhibition against E. coli, and the Hot Aqueous extract showed no effect at 50% and 25%, and slight inhibition at 100% and 75%. For Candida albicans, the Ethanol extract showed minimal inhibition at all concentrations and no effect at 25%. The Aqueous extract had a slight effect at 100% and no inhibition at 75%, 50%, and 25%.